Young people in care and criminal behaviour - Fitzpatrick, Claire, 1976- (London ; Philadelphia : Jessica Kingsley Publishers, 2006)
Society holds a mistaken perception that links children in public care with criminal activity. This book addresses the lack of evidence supporting this potentially damaging assumption, analysing past research, critically examining current policy and combining theoretical insights from the disciplines of childcare and criminology.
Introduction -- What do we know about experiences of care -- and after? -- The current policy climate -- Introducing the research study -- Exploring the residential care experience -- Developing secure attachments in the context of care -- Experiences of education -- Life after care : coping with independence -- Key findings and implications for policy and practice.
Includes bibliographical references (pages 189-197) and indexes.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Youth -- Institutional care -- Great Britain; Foster children -- Great Britain; Criminal behavior, Prediction of -- Great Britain; Juvenile delinquency -- Great Britain; Jeunesse -- Soins en institutions -- Grande-Bretagne.; Délinquance juvénile -- Grande-Bretagne.; POLITICAL SCIENCE -- Public Policy -- Social Services & Welfare; POLITICAL SCIENCE -- Public Policy -- Social Security; Criminal behavior, Prediction of; Foster children; Juvenile delinquency; Youth -- Institutional care; Great Britain